2016
DOI: 10.1080/2162402x.2016.1249553
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25hiCD127 Treg and CD4+CD45R0+CD49b+LAG3+ Tr1 cells in bone marrow and peripheral blood samples from children with neuroblastoma

Abstract: Metastatic spread in the bone marrow (BM) at diagnosis is the worst prognostic factor for neuroblastoma (NB) patients. Here, we analyzed the presence of two immunosuppressive cell subsets, CD4 C CD25 hi CD127 ¡ regulatory T (Treg) cells and CD4 C CD45R0 C CD49b C LAG3 C type 1 regulatory (Tr1) cells, in BM and peripheral blood (PB) samples from NB patients and controls. Frequency of both regulatory cell subsets was lower in BM and PB samples from NB patients than in respective healthy controls. No correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Indeed, anti-CD4 mAb treatment showed activity in CD4 + T cell lymphomas, without significantly increasing the risk of life-threatening infections 42 , 43 . However, the role of CD4 + immune regulatory T cell subsets is still debated in NB patients and controversial data on the potential role of Treg have been reported 44 46 , while CD4 + LAG-3 + Tr1 cells seemed reduced 46 . Finally, further studies in pre-clinical models should be considered to confirm the possible efficacy of this novel therapeutic strategy before clinical testing in patients with refractory or relapsing NB.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, anti-CD4 mAb treatment showed activity in CD4 + T cell lymphomas, without significantly increasing the risk of life-threatening infections 42 , 43 . However, the role of CD4 + immune regulatory T cell subsets is still debated in NB patients and controversial data on the potential role of Treg have been reported 44 46 , while CD4 + LAG-3 + Tr1 cells seemed reduced 46 . Finally, further studies in pre-clinical models should be considered to confirm the possible efficacy of this novel therapeutic strategy before clinical testing in patients with refractory or relapsing NB.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown an increased number of circulating Treg cells in patients with neuroblastoma compared to healthy individuals, but was not prognostic of outcomes ( 86 , 87 ). In another report, lower frequency of Treg cells has been observed in the bone marrow and peripheral blood samples of patients with neuroblastoma compared to healthy controls ( 88 ). Interestingly, a higher proportion of Treg cells in the bone marrow and peripheral blood correlated with MYCN amplification ( 88 ).…”
Section: Tumor Microenvironment Of Neuroblastomamentioning
confidence: 93%
“…In another report, lower frequency of Treg cells has been observed in the bone marrow and peripheral blood samples of patients with neuroblastoma compared to healthy controls ( 88 ). Interestingly, a higher proportion of Treg cells in the bone marrow and peripheral blood correlated with MYCN amplification ( 88 ).…”
Section: Tumor Microenvironment Of Neuroblastomamentioning
confidence: 93%
“…Morandi and colleagues found that Treg (CD4+CD25hiCD127−) and Tr1 (CD4+CD45R0+CD49b+LAG3+) subsets are decreased in NBL patients compared to controls, but no correlation was found with prognostic factors, such as age and stage. MYCN amplification was the only prognostic factor associated with higher levels of Treg numbers in BM and Tr1 levels in PB [41]. In addition, CD4+ and CD8+ T cells show increased surface expression levels of the checkpoint inhibitor CTLA-4, and PD-1 on CD4 T cells.…”
Section: Immune Cells In Peripheral Bloodmentioning
confidence: 95%